2022
DOI: 10.1007/s00384-022-04153-3
|View full text |Cite
|
Sign up to set email alerts
|

Application of PREVENA (Surgical Incision Protection System) in reducing surgical site infections following reversal of ileostomy or colostomy: the PRIC study protocol

Abstract: Aim There is a current lack of evidence in the literature to support the routine use of negative pressure wound therapy (NPWT) to reduce the risk of surgical site infections (SSI) in the setting of ileostomy or colostomy reversal. The aim of this study is to examine whether routine NPWT confers a lower rate of SSI than conventional dressings following reversal of ileostomy or colostomy. Methods The PRIC study is a randomized, controlled, open-label, multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In clinical practice, it is worth exploring strategies to mitigate the risk of surgical site infections following ileostomy or colostomy reversal. Several randomized controlled trials have substantiated the efficacy of routine employment of negative pressure wound therapy in reducing the incidence of SSIs after ileostomy or colostomy reversal [ 36 , 37 ]. The widespread adoption and practicality of this technique warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, it is worth exploring strategies to mitigate the risk of surgical site infections following ileostomy or colostomy reversal. Several randomized controlled trials have substantiated the efficacy of routine employment of negative pressure wound therapy in reducing the incidence of SSIs after ileostomy or colostomy reversal [ 36 , 37 ]. The widespread adoption and practicality of this technique warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the authors reported rapid formation of granulation tissue and reduction of bacterial load 3 . Since its introduction, several studies have compared NPWT with conventional dressing methods, reporting improved wound healing rate and time [4][5][6][7][8][9][10][11][12] , especially in general surgery. The promising effects of NPWT in complex wound healing led to a broadening of its indications 1 .…”
Section: Introductionmentioning
confidence: 99%